The Effect of Profitability, Liquidity, and Leverage Ratio on Stock Prices in the State-Owned Banking Sector in Indonesia - Putri Azizah Sahirah; Citra Ayni Kamaruddin; Sri Astuty; Regina Regina; Basri Bado (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Stocks represent a capital market instrument with the potential to generate high returns. When making investment decisions, investors typically assess various internal aspects of a company, including its financial performance. The objective of this study is to examine the influence of profitability, liquidity, and leverage ratios on stock prices in the Indonesian banking sector, with a particular focus on state-owned banks, in both partial and simultaneous regression models. The methodology employed is quantitative analysis, with a secondary data set being utilized. The sample was determined using a purposive sampling technique, covering four state-owned banks (BRI, BNI, Mandiri, and BTN) for the 2010-2024 period. The findings of the analysis demonstrate that profitability and leverage exert a substantial negative influence on the stock prices of these banking institutions, while the liquidity ratio does not demonstrate a significant effect. Concurrently, all three variables exert an influence on stock prices, with an R-squared value of 58%.